Proyecto de factibilidad para la creación de una empresa productora y comercializadora de cerveza artesanal sin alcohol en la ciudad de Latacunga. - Chávez Páez, Nicole Lisseth (2023)
The present project entitled “Feasibility project for the creation of a company to produce and market alcohol-free craft beer in the city of Latacunga” had the following objectives, their phases and importance; to prepare a market study and a technical study for the non-alcoholic beer production and marketing company; and to conduct a financial study and evaluation to determine the feasibility of the business. The methodology used was bases on a descriptive quantitative approach, using the deductive method. The population considered was composed of 80,659 inhabitants of the city of Latacunga, corresponding to 18 years of age and older, and a sample of 382 people was obtained statistically, to whom a survey was applied in order to determine the market study. This project showed its feasibility with a Net Present Value (NPV) of $ 238,723.99 an Internal Rate of Return (IRR) of 33, 82% higher than the ARR of 13.82%. The payback period obtained was 1 year 8 months 5 days and the cost benefit ratio was 1.34.